The high cost of celiac disease in an Israeli Health Maintenance Organization - Anthony D. Heymann; Moshe Leshno; Ronit Endevelt; Raanan Shamir (Health Economics Review, 2013)
Background: The aim of this study was to identify costs in patients diagnosed with Celiac disease. Methods: This retrospective case control study covered the period 2003-2006 and was conducted in a large Israeli Health Maintenance Organization insuring over two million members. Our cohort comprised 1,754 patients with Celiac disease with a control group of 15,040. Costs were aggregated according to main cost-branches and computed individually for each member. A linear step wise regression was performed with costs being the dependent variable and the independent variables; age, gender and the presence of celiac disease. Costs were compared with patients suffering from other chronic diseases. Results: The total costs of the patients with celiac disease were significantly higher than that of the control group for hospital admission, medications, laboratory and imaging. Hospital admission rate was 7.98% as opposed to 7.1% for the control group (p = 0.06). When compared with other chronic illnesses, the costs of patients with celiac disease were similar to those of patients with diabetes and hypertension. Conclusions: Patients with Celiac disease utilize medical services more than the general population. This research suggests that the use of medical resources by patients with Celiac disease may be higher than previously thought.
Keywords: 330; Celiac disease; Costs and cost analysis; Health Maintenance Organization